Capital Requirements and Business Cycles with Credit Market Imperfections - Agénor, P.-R.; Alper, K.; Pereira da Silva, L. (2012)
The business cycle effects of bank capital regulatory regimes are examined in a New Keynesian model with credit market imperfections and a cost channel of monetary policy. Key features of the model are that bank capital increases incentives for banks to monitor borrowers, thereby reducing the probability of default, and excess capital generates benefits in terms of reduced regulatory scrutiny. Basel I and Basel II-type regulatory regimes are defined, and the model is calibrated for a middle-income country. Simulations of supply and demand shocks show that, depending on the elasticity that relates the repayment probability to the capital-loan ratio, a Basel II-type regime may be less procyclical than a Basel I-type regime.